Problem Based Learning (PBL) Video Learning Based on Energy Source Material Videoscribe - Rio Ananta, I Gede; Luh Putu Sri Lestari (Mimbar Ilmu, 2023)
Learning media plays a vital role in learning activities to achieve the goals of learning activities. However, most teachers still need to use media more, causing low student learning outcomes. Thus, supporting media is necessary for learning. This research aims to create learning videos for the Problem-Based Learning model based on VideoScribe for science content. The type of study used is development research with the ADDIE model. Product trials were conducted to test product validity by material and media experts, teachers conducted practicality tests, and effectiveness tests were given to students using a one-group pretest-posttest design. Data collection methods are questionnaires and tests. The data analysis technique used is qualitative and quantitative descriptive analysis. The study results obtained validity according to media experts at 4.70, learning design experts at 4.75, practicality of practitioner responses at 4.80, individual trials at 4.60, and small group trials at 4.62 in the outstanding category. Effectiveness testing found that the media was significantly effective. These results align with the study's aim to obtain valid and effective learning videos. The research concludes that PBL model learning videos based on VideoScribe with science content are declared valid and effective in learning activities to improve science learning outcomes for third-grade elementary school students.